Lumen maintenance predictions for LED packages. (July 2016) - van Driel, W.D.; Schuld, M.; Jacobs, B.; Commissaris, F.; van der Eyden, J.; Hamon, B.
Abstract: Commercial claims for LED-based products in terms of lumen maintenance are fully based on TM-21 extrapolations using LM-80 data. This paper indicates that there may be a risk in doing this as TM-21 only relies on the behavior of the average LED degradation, instead of taking into account the degradation of all individual LEDs. Therefore, we propose a more profound statistical analysis in order to make the appropriate step from TM-21 extrapolation to lumen maintenance on a product level. This is needed as some commercial claims are based on 10 years of warranty and some service bids provide periods of 20 to 25 years of operation. This paper reviews the different approaches currently available to perform lumen maintenance extrapolations. We propose a new method to analyze and extrapolate LM-80 data using a more profound statistical approach. Highlights: A new statistical method to extrapolate LM-80 data The method outperforms the currently available ones as it is statistically founded. Five cases were executed and benchmarked with the TM-21 method. A full statistical acceleration model is now available for lifetime assessment of LEDs.